2016
DOI: 10.1097/igc.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Genetics Attendance at a Gynecologic Oncology Tumor Board on Referrals for Genetic Counseling and BRCA Mutation Testing

Abstract: Patients with ovarian cancer had a high rate of BRCA mutations. Attendance of a genetics service at a tumor board was associated with an improved rate of referral of patients for genetic counseling and BRCA mutation testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
1
30
2
Order By: Relevance
“…Compared with our previous report for the period 2013–2015,10 the proportion of patients referred for genetic testing in the current study has almost doubled from 40.6% to 78.6%. Factors that likely contributed to this change were increased awareness among clinicians treating women with non-mucinous epithelial tubo-ovarian cancers following the introduction in 2016 of the poly-(ADP-ribose) polymerase inhibitor Olaparib; the introduction of additional pathways for genetic counseling and testing such as mainstreaming and tele-counseling; and the attendance of genetic counselors from the Familial Cancer Clinic at the weekly tumor board who recorded eligible patients and followed up referrals from the treating clinicians if a referral had not been received after 6 weeks.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Compared with our previous report for the period 2013–2015,10 the proportion of patients referred for genetic testing in the current study has almost doubled from 40.6% to 78.6%. Factors that likely contributed to this change were increased awareness among clinicians treating women with non-mucinous epithelial tubo-ovarian cancers following the introduction in 2016 of the poly-(ADP-ribose) polymerase inhibitor Olaparib; the introduction of additional pathways for genetic counseling and testing such as mainstreaming and tele-counseling; and the attendance of genetic counselors from the Familial Cancer Clinic at the weekly tumor board who recorded eligible patients and followed up referrals from the treating clinicians if a referral had not been received after 6 weeks.…”
Section: Discussioncontrasting
confidence: 83%
“…Of note, despite the significant increase in the proportion of patients referred for genetic testing, the proportion of patients who subsequently declined testing remains similar at 16.4% compared with 19.4% in our previous study 10. During the study period the poly-(ADP-ribose) polymerase inhibitor Olaparib was only licensed in Australia for women with platinum-sensitive disease at relapse, and hence there may have been less incentive for patients who were reluctant to consider genetic testing after completion of first-line therapy.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Despite care of the family being central to the values and ethos underpinning palliative care [34], genetics appeared to be missing from the palliative agenda due to assumptions amongst providers that genetic issues will have already been addressed earlier in the disease trajectory. This assumption is flawed, given that numerous studies have identified suboptimal genetic referral rates within the oncology setting, with genetic issues often being overlooked at the time of initial diagnosis [6,8]. Furthermore, patients with particularly aggressive cancers may not present until the advanced stages of their disease [8], and concerns about the family history may only surface as the affected individual becomes increasingly unwell [21].…”
Section: Discussionmentioning
confidence: 99%